The Relationship between the Application of Social Distancing and the Achievement of Adolescent Social Development Tasks During the COVID-19 Pandemic at Kemala Bhayangkari 1 Junior High School Medan - Rahmawati, Ria; Daulay, Wardiyah (TALENTA Publisher, 2023)
The phenomenon in the field during the COVID-19 pandemic that restricts students from carrying out activities in schools, conducting online learning which has now begun to do limited face-to-face learning while still carrying out social distancing rules so that there are still teenagers who have not been able to solve their problems correctly. This results in the task of adolescent social development needing to be improved. This study aims to identify whether or not there is a relationship between the application of social distancing and the achievement of adolescent development tasks during the COVID-19 pandemic at SMP Kemala Bhayangkari 1 Medan. This research design is descriptive quantitative using Non-Probability Sampling (Purposive Sampling) technique. That is, the sample is selected according to what the researcher wants. The results were that teenagers who implemented social distancing during the COVID-19 pandemic at Kemala Bhayangkari Junior High School were categorized as obedient as 38 teenagers (57.6 %) and 35 teenagers (53%). The conclusion is that there is a significant relationship between the direction of a positive relationship and a reasonably good strength between social distancing and the achievement of adolescent social development tasks. This means that in the COVID-19 pandemic, teenagers who obediently apply social distancing can achieve their social development tasks quite well. This can mean that some teenagers must still achieve their developmental tasks well. It is recommended that teenagers continue to learn to understand the importance of implementing social distancing and achieving the tasks of adolescent social development that must be realized properly and optimally so that they can adapt to their surrounding environment.